The role of vocabulary knowledge on inference generation: A meta-analysis - Sterpin Lucas Federico (Sciendo, 2021)
Successful text comprehension results in a coherent mental model of the situation being described. To achieve this, the reader has to infer certain information by connecting parts of the text to their prior knowledge. An important construct involved in this process is vocabulary knowledge, usually divided into breadth and depth. We conducted a meta-analysis on 23 studies, and explored the fit of five different models to establish an effect size of both dimensions of vocabulary on inference making, as well as its developmental trajectory in children aged 3-12. We found a significant and moderate effect of vocabulary knowledge of both modalities. Vocabulary type was not a significant moderator, but age was, meaning that there was a similar effect for both breadth and depth and that the strength of the correlations decreased with age. Heterogeneity was high overall, meaning that more moderators should be assessed in future studies.